Profile of serum cytokine concentrations in patients with gouty arthritis - Tie Zhang (SAGE Publishing, 2021)
Objective This study aimed to analyze the changes in serum inflammatory cytokines and anti-inflammatory cytokines in patients with gouty arthritis (GA). Methods The clinical data and serum samples in patients with gouty arthritis and those in healthy volunteers were collected in China-Japan Friendship Hospital from July 2018 to January 2019. Serum cytokine concentrations in patients with GA and volunteers (controls) were determined by a chemiluminescence method. The differences in cytokine concentrations were compared between the two groups. Results Concentrations of serum interleukin-1 beta (IL-1ß), tumor necrosis factor-alpha (TNF-α), IL-6, IL-8, and IL-4 were significantly higher in patients with acute GA than in controls. Serum concentrations of IL-1ß, TNF-α, IL-6, IL-8, and immunoglobulin E in patients with remission of GA were significantly lower, whereas concentrations of IL-10 and interferon-γ were significantly higher, compared with those in patients with acute GA. Conclusion This study shows that serum concentrations of IL-1ß, TNF-α, IL-6, IL-8, and IL-4 are significantly elevated in patients with GA, and may be involved in the pathogenesis of GA.